2011
DOI: 10.1021/jf200689r
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reference Genes for Gene Expression Studies in Zucchini (Cucurbita pepo) Using qPCR

Abstract: The zucchini (Cucurbita pepo) is an important food crop, the transcriptomics of which are a fundamental tool to accelerate the development of new varieties by breeders. However, the suitability of reference genes for data normalization in zucchini has not yet been studied. The aim of this study was to assess the suitability of 13 genes for their potential use as reference genes in quantitative real-time PCR. Assays were performed on 34 cDNA samples representing plants under different stresses and at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 38 publications
4
71
0
Order By: Relevance
“…Under temperature treatment, EF1a was the most stably expressed gene in A. annua, and the results were consistent with the previously reported results from chrysanthemum, a plant species belonging to the family of Compositae (Gu et al 2011). EF1a was also recommended to be the suitable reference gene under the treatment of plant growth regulators in zucchini (Obrero et al 2011) and Catharanthus roseus (Wei 2010). In MeJA or ABA treatment, EF1a was the most stably expressed gene among the ten candidate reference genes.…”
Section: Discussionsupporting
confidence: 89%
“…Under temperature treatment, EF1a was the most stably expressed gene in A. annua, and the results were consistent with the previously reported results from chrysanthemum, a plant species belonging to the family of Compositae (Gu et al 2011). EF1a was also recommended to be the suitable reference gene under the treatment of plant growth regulators in zucchini (Obrero et al 2011) and Catharanthus roseus (Wei 2010). In MeJA or ABA treatment, EF1a was the most stably expressed gene among the ten candidate reference genes.…”
Section: Discussionsupporting
confidence: 89%
“…These advantages allow a straightforward comparison and make it become the most appropriate choice for gene expression analysis (Garson et al 2005;Li et al 2010;Martin et al 2008). Despite its numerous advantages, several serious flaws have been reported, including the lack of reliable reference genes for normalization (Obrero et al 2011). To obtain reliable results, normalization is crucial for RT-qPCR studies to control for sample differences (Tong et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these genes are commonly used for normalization without any validation (Brunner et al 2004;Chi et al 2012;Marum et al 2012). However, a few recent studies have shown that the widely used reference genes vary considerably in response to some specific experimental conditions (Marino et al 2008;Morgante et al 2011;Nicot et al 2005), that if not chosen properly, the reference genes may be unsuitable for normalization purposes owing to large measurement errors (Dekkers et al 2012;Obrero et al 2011). Therefore, to ensure proper normalization, it must be demonstrated that the reference genes of choice have high expression stability independent of the varying experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the selection of reference genes in tomato, Fagopyrum esculentum developmental stages, and soybean under varied light regimes (Expósito-Rodríguez et al, 2008;Hu et al, 2009;Demidenko et al, 2011) also identified TIP as the most stable reference gene for vegetative samples. In previous studies, Clathrin has also been identified as the best candidate for normalization (Expósito-Rodríguez et al, 2008;Obrero et al, 2011).…”
Section: Discussionmentioning
confidence: 99%